Structural Modeling in Green Supply Chain Management Practices under Chains of Qualitative Indices - Sahu, Atul Kumar; Narang, Harendra Kumar; Rajput, Mridul Singh (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*307.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976808);" role="presentation">The successfully execution of any <span dir="ltr" style="left: calc(var(–scale-factor)*222.41px); top: calc(var(–scale-factor)*307.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.988209);" role="presentation">business is today’s dynamic era is possible by integrating the zone of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95797);" role="presentation">environmental thinking in the business activities. Green Supply Chain Management (GSCM) is a significant <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904679);" role="presentation">view, which needs to be integrated with core business proceedings <span dir="ltr" style="left: calc(var(–scale-factor)*340.87px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896351);" role="presentation">for the sake o<span dir="ltr" style="left: calc(var(–scale-factor)*395.26px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904);" role="presentation">f executing sustainable bu<span dir="ltr" style="left: calc(var(–scale-factor)*499.44px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.846406);" role="presentation">siness <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961291);" role="presentation">in today’s market life. <span dir="ltr" style="left: calc(var(–scale-factor)*165.41px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958158);" role="presentation">GSCM is the incorporation of environmental thinking into diverse arena of the Supply <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*360.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.992818);" role="presentation">Chain Management (SCM). Thus, in this study, the authors presented a framework for modeling GSCM <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*374.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944492);" role="presentation">practices by cons<span dir="ltr" style="left: calc(var(–scale-factor)*144.74px); top: calc(var(–scale-factor)*374.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.995764);" role="presentation">idering the chains of qualitative Indices. The implication of fuzzy sets theory along with <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00788);" role="presentation">DEMATEL (Decision-<span dir="ltr" style="left: calc(var(–scale-factor)*166.73px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.999495);" role="presentation">Making Trial and Evaluation Laboratory) technique under the domain of GSCM is <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*400.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.983057);" role="presentation">presented in this work. Modeling based on momentous decisive factor r<span dir="ltr" style="left: calc(var(–scale-factor)*381.10px); top: calc(var(–scale-factor)*400.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.990513);" role="presentation">esponsible for driving the GSCM <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*413.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937962);" role="presentation">network is presented in this study. The authors shaped an approach for addressing the green practices under <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*427.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967726);" role="presentation">uncertainty and impreciseness for the manufacturing firms. The major intension of the proposed work is to <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.880305);" role="presentation">enlarge <span dir="ltr" style="left: calc(var(–scale-factor)*108.00px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944462);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*127.09px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9312);" role="presentation">views <span dir="ltr" style="left: calc(var(–scale-factor)*157.07px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*172.17px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*191.00px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.8555);" role="presentation">researchers <span dir="ltr" style="left: calc(var(–scale-factor)*242.68px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869552);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*263.90px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.855947);" role="presentation">readers <span dir="ltr" style="left: calc(var(–scale-factor)*299.49px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908336);" role="presentation">towards <span dir="ltr" style="left: calc(var(–scale-factor)*337.86px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919719);" role="presentation">developing a <span dir="ltr" style="left: calc(var(–scale-factor)*400.10px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908909);" role="presentation">mathematical <span dir="ltr" style="left: calc(var(–scale-factor)*460.67px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942023);" role="presentation">framework <span dir="ltr" style="left: calc(var(–scale-factor)*511.24px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*453.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.974342);" role="presentation">implementing GSCM by the concerned firms. <span dir="ltr" style="left: calc(var(–scale-factor)*274.27px); top: calc(var(–scale-factor)*453.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.979704);" role="presentation">An index based on fuzzy information is presented and the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*466.63px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931918);" role="presentation">computational effort for modeling the green practices is presented, s<span dir="ltr" style="left: calc(var(–scale-factor)*351.91px); top: calc(var(–scale-factor)*466.63px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90883);" role="presentation">o that the managers can easily understand <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*479.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905948);" role="presentation">the proposed work and can model green practices in their decision making